Answer :

y=e2x(a+bx)=ae2x+bxe2x


Differentiating with respect to x,


y’=2ae2x+be2x+2bxe2x

y’=2y+be2x ..........(1)


Differentiating with respect to x,


y’’=2y’+2be2x

.........(2)


Substituting (2) in (1), we get,



⇒ 2y’=4y+y’’-2y’


y’’-4y’+4y=0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve the differeMathematics - Board Papers

The general solutMathematics - Exemplar

The differential Mathematics - Exemplar

Form the differenMathematics - Board Papers

Solve the differeMathematics - Exemplar

Given that Mathematics - Exemplar

Find the equationMathematics - Exemplar